Nanostructure Semiconductor Optical Amplifiers Building Blocks for All-Optical Processing - Rostami, Ali. (Engineering Materials,, 2011)
"Nanostructure Semiconductor Optical Amplifiers" reviews all-optical processing methods currently available and presents semiconductor optical amplifiers (SOAs) as a new building block for this purpose. The authors discuss the overcomes of high frequency operation of SOAs and propose a new all-optical pumping method for the implementation of semiconductor optical amplifiers.